Breaking the Constitutional Silence: the Public Services Industry and Government. Issue 3 (19th May 2016) - Johal, Sukhdev; Moran, Michael; Williams, Karel
Abstract: Analysis of constitutional arrangements has been too narrow in the past, confined to examination of explicitly governmental arrangements. But corporate enterprises perform such important public functions, especially in the age of outsourcing, that they need to be incorporated into the constitution. The article develops this argument and proposes a framework for such incorporation.